Analysis of F2 Population of Intraspecific CC Genome Oryza by using SSR Marker (Plant Tissue Culture and Biotechnology, 2008)
Of the 22 Oryza species, three are diploid CC genome species and six are allotetraploid species sharing the CC genome. The diploid CC genome species have useful genes such as those conferring resistance to brown plant hopper, white back plant hopper, bacterial blight and yellow dwarf virus disease. This work describes SSR marker analysis of progeny derived from crosses in O. eichingeri (CC genome). Twelve Microsatellites or Simple Sequence Repeats (SSR) markers have been used to analyze 82 F2 progeny plants from an intraspecific cross, O. eichingeri (Uganda) x O. eichingeri (Sri Lanka). The markers were distributed on 8 of the 12 linkage groups. Most of the SSR markers had the expected distribution of plants segregating for the parental or heterozygous condition except for RM109 which was present in more individuals with the genotype of the parent from Sri Lanka than the heterozygous or Uganda parent. The F2 population showed transgressive segregation for days to heading. Some characters had a normal distribution such as internode color and leaf size. Other characters showed segregation toward one of the parents viz. panicle type toward the Uganda parent and auricle color and leaf morphology toward the Sri Lankan parent.Key words: SSR marker, F2 population, Intraspecific hybrid, CC genome, OryzaDOI = 10.3329/ptcb.v16i1.1104Plant Tissue Cult. & Biotech. 16(1): 37-43, 2006 (June)